Early stenosis of bioprosthetic mitral valve during venoarterial extracorporeal life support successfully treated using isolated percutaneous balloon valvuloplasty: a case report. Issue 1 (17th January 2018) - Nowacka, Anna; Eeckhout, Eric; Tozzi, Piergiorgio; Kirsch, Matthias
Abstract: We present the case of a 58-year-old man who had complex reoperative bioprosthetic mitral valve replacement under femorofemoral venoarterial extracorporeal life support. The patient experienced early bioprosthetic valve failure due to leaflet fusion. This complication could be treated successfully using isolated percutaneous balloon valvuloplasty that allowed restoration of full leaflet mobility.